Mobile Health Quality among National Health Insurance Participants in South Sumatra (KEMAS: Jurnal Kesehatan Masyarakat, 2020)
The development of information technology and telecommunications has penetrated into various sectors including health. With Mobile JKN, community administrative activities in managing JKN are easier. The study aims to analyze the perception of mobile health among participants JKN in South Sumatra Province. This research is a quantitative study with a cross-sectional design. The research sample was JKN participants stay in South Sumatra aged 18 years who use the Mobile JKN app amount 400 participants. The sampling technique used purposive sampling. Data collection using online questionnaires and distributed through social media. Results of the study showed that the perception of the quality system has optimal results (50,50%). The problem encountered was in the network stability indicator from JKN mobile application users. On the quality of information has optimal results(67.50%).Problems encountered are in the indicator of limited service information, display updates. Then, the quality of service has optimal results (63,50%). The problem encountered was in the service integration indicator from the JKN mobile application. Quality of the JKN Mobile application seen from the System Quality, Information Quality and Service Quality has optimal results. BPJS Health suggested to increase network stability, improve service information, display updates and information in the JKN Mobile application, conduct application socialization, and develop service integration.